1988
DOI: 10.1139/p88-122
|View full text |Cite|
|
Sign up to set email alerts
|

Production of metastable and resonant atoms in rare-gas (He, Ne, Ar) radio-frequency and microwave-sustained discharges

Abstract: Radial density distributions of excited atoms in plasma columns of helium, neon, and argon, sustained by a travelling electromagnetic surface wave, are examined as a function of frequency over the range 200 kHz – 2450 MHz. This investigation is conducted using an end-on measurement method. At low frequencies (<50 MHz), these radial distributions show a maximum at the axis (J0 Bessel-like behavior), whereas as frequency is increased beyond 50 MHz up to 2450 MHz, the radial distributions flatten and finally e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 1 publication
0
13
0
1
Order By: Relevance
“…Experimental implementation of the spectral-lamp absorption method is easier and less expensive than the diode laser technique, but it depends on the spectral profile of the absorption line, which turns from Gaussian at low enough gas pressure to the Voigt type at atmospheric pressure. At low pressures, the absorption method employing a spectral lamp is well documented and extensively used [2,[19][20][21][22][23][24][25][26][27]. The current work extends this method to higher-pressure plasmas (N1 kPa), including those at atmospheric pressure.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Experimental implementation of the spectral-lamp absorption method is easier and less expensive than the diode laser technique, but it depends on the spectral profile of the absorption line, which turns from Gaussian at low enough gas pressure to the Voigt type at atmospheric pressure. At low pressures, the absorption method employing a spectral lamp is well documented and extensively used [2,[19][20][21][22][23][24][25][26][27]. The current work extends this method to higher-pressure plasmas (N1 kPa), including those at atmospheric pressure.…”
Section: Introductionmentioning
confidence: 95%
“…The density of metastable and resonant atoms can be determined in various ways: self-absorption [7][8][9][10][11] and absorption using the emission from a tunable diode laser [12][13][14][15][16][17][18] or the line from a spectral lamp [2,[19][20][21][22][23][24][25][26][27]. Utilizing lasers to determine the density of metastable and resonant atoms is advantageous, as it does not depend on the absorption-line spectral profile.…”
Section: Introductionmentioning
confidence: 99%
“…However, the monotonic increase of the dissociation degree was traced with increasing electron density, and its relative increment with N e is reproduced in the present model fairly well. One of the reasons for this disagreement is the assumption of the radial dependence of the electron density in the present numerical modeling, i. e., the Bessel J 0 distribution of the electron density, whereas several experiments showed that the real electron distribution was rather flat over the discharge tube, or that the electron density of the inner side is rather lower in the microwave discharge tube [16]. Another possible reason lies in the experimental side, that is, the interpretation of the actinometry measurement where we inevitably assume the corona equilibrium for the actinometry level of the oxygen atom, even though we include the quenching process of the actinometric level by collisions with the background molecules because of rather high-discharge pressure, 1 Torr [4,5].…”
Section: Resultsmentioning
confidence: 82%
“…H.F discharges with external cavities are shown in Fig 5a with optical arrangements for spatial distributions diagnostics of excited states [5]. The plasma column is sustained by the electric field of a surface wave which is launched by a high frequency structure called Ho-box for frequencies ranging from 0.2 to 900 MHz and by a waveguide-surfatron at 2450 MHz (insert in Fig 5a).…”
Section: 3/hmentioning
confidence: 99%